Pengaruh Pemanfaatan Laboratorium dan Nilai Karakter Terhadap Hasil Belajar IPA Siswa Kelas VIII - Nur Hikmah; Kiki Nurzila (KULIDAWA, 2022)
This study aims to determine the effect of laboratory utilization and character values on science learning outcomes for SMPN 2 Bonegunu students. This research is a quantitative study with a research sample of all students in class VIII as many as 50 students. This study used 2 types of instruments, namely instruments to measure character values in the form of test questions and instruments to measure laboratory utilization in the form of questionnaires. The data analysis technique used is descriptive analysis technique. The results showed that: there was an effect of using the laboratory on student science learning outcomes, with a significant value of 0.000 <0.05, with a contribution of 96.7% and there was an effect of character values on student science learning outcomes with a significant value of 0.007 <0.05, with a contribution of 96.7%. It can be concluded that the utilization of the character value laboratory influences the learning outcomes of Class VIII students of SMPN 2 Bonegunu.Keywords: Laboratory Utilization, Character Value, Science’s Learning Outcomes